La vicenda della morte di Carlo e Giovanni Carafa in alcuni testi di fine Cinquecento e Seicento - Boni, Fabio (Romanica Silesiana, 2020)
The article presents the story of the death of Carlo and Giovanni Carafa, leading figures at the papal court, condemned to death by Pius IV, in 1561. Article analyses three unpublished texts (from the 16th and 17th century) that reconstruct the facts, focusing on their different perspectives and functions.